KÜLÖNBÖZŐ ÉTRENDEK, DIÉTÁK HATÁSA A SPORTTELJESÍTMÉNYRE - Sarang, Zsolt; Gyenes, Dominik (Stadium - Hungarian Journal of Sport Sciences, 2021)
The fuel of the human body is food, more specifically the nutrients it contains, so even non-athletes need to pay close attention to what they eat. It is even more important for athletes to develop performance-optimizing eating habits. Sport nutrition is one of the biggest opportunities for performance optimization that has become more and more important recently. There are many special diets, perhaps the best known are: ketogenic diet, Mediterranean diet, vegetarianism, paleo diet. We need to choose our diet while maintaining good health. We should not forget that a long-distance runner, for example, may need a completely different diet than a weightlifter. However, no two people are the same, individuals have different genetics, weight, body composition, movement intensity, metabolism, and the goal they want to achieve, which is why an individualized diet combination within each sport results in the best performance. In our study, we aimed to analyze the effect of diets of different compositions on sports performance based on the mentioned aspects. In the course of our work, we collected and reviewed relevant content on Google and Pubmed. Overall, it can be said that developing the right diet can be a multiplier return on investment. Sport as a physical activity determines lifestyle, including nutrition. Proper, balanced nutrition is essential for both athletes and non-athletes